Eksplorasi pemenuhan kebutuhan berbasis reliji bagi wisatawan perempuan Muslim dalam memengaruhi keputusan bepergian ke negara-negara minoritas Muslim - DWIPUTRANTO, ANDI (Journal of Islamic Economic and Business Studies, 2023)
The purpose of our descriptive research is to gain accurate situations on how the fulfillment of Muslim women travelers’ faith-based needs and requirements influences their decisions to travel to Muslim-minority countries. Semi-structured interviews are conducted on selected Muslim women travelers who had recent travel to Muslim-minority countries. In according with the theory of planned behavior, Muslim women traveling are influenced by subjective norms, namely their religion. They will try to follow the rules of their religion and the experience gained in a tourist destination country, however, will be a consideration for coming back again.Based on the description of how Muslim women practice their religion while traveling, provide suggestions for related parties. Countries that are visited by many Muslims need to provide facilities related to worship, both places and also supporting facilities such as clean water. Information about the existence of places of worship, and places that sell halal food needs to be reproduced. This effort also needs to be a concern of travel agents. Information about local cultures, including food, can be included with information on non-halal activities so that Muslims can anticipate them